The degree of achieving the international accreditation standards (CAEP) in the mathematics teacher preparation curricula in the faculties of basic education from the viewpoint of the faculty members (Journal of the College of Basic Education, 2022)
The aim of the research is to find out the degree achieved after the international accreditation (CAEP) in the benefits of preparing the mathematics teacher in Basic Arabic from the face of the members of the school board and your family did not Who is made up of the machine? Distributed on 5 axes, commentator, director ofSaying and Imprisonment Methods of Training Westin Methods Values, services and international accreditation, in the objectives of the program equipment were applied to a sample It consists of (26 teaching staff from the Faculty of Islamic Education, Department of Mathematics, and Al-Saj revealed that Duff the subject and not admission and registration, teaching methods and teachingmethods, and you will meet the standards of columns An intermediary approach from the place of return in life and women in the cases of students to a moderate degree as The crown is the presence of sensory-significant differences between the components of the living organisms about the determinations of the availability of resources .Emad International in God one Nudity of sex and academic specialization, inAvailability with international accreditation related services Axis repositioning Logi hammt the quality of habits and production process